2022
DOI: 10.2478/revecp-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

The firm-specific and macroeconomic determinants of the financial structure of construction companies in selected European countries

Abstract: This research builds on previous studies in the field of financial structure and develops knowledge for the construction industry in eight selected countries in Central and Eastern Europe – Visegrád Group, Austria, Bulgaria, Slovenia, and Romania. The aim of the research is to examine the influence of profitability, asset structure, the GDP growth rate and the reference interest rate on the level of total, long-term and short-term debt of companies. The research period is from 2009 to 2018. The main conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Moreover, with the value of the Hansen test in GMM, one can easily observe the validity of instrumental variables (IV). Additionally, numerous scholars employed the two-step system GMM in the most recent studies (Yousaf, 2023a;Rehman et al, 2022;Gul et al, 2022;Růčková and Škuláňová, 2022;Oppong et al, 2019). Consequently, we also employed the two-step system GMM to estimate Model 1 and Model 2 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, with the value of the Hansen test in GMM, one can easily observe the validity of instrumental variables (IV). Additionally, numerous scholars employed the two-step system GMM in the most recent studies (Yousaf, 2023a;Rehman et al, 2022;Gul et al, 2022;Růčková and Škuláňová, 2022;Oppong et al, 2019). Consequently, we also employed the two-step system GMM to estimate Model 1 and Model 2 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These investigations have, however, mainly been performed within one industry or using simple industry dummies across industries. Studies have focused on the statistical and economic significance of estimated coefficients but not on the reasons for the difference in leverage, which goes beyond such an analysis, in cases where single industries have not been examined, such as construction (Ruckova and Skulanova 2022), tourism (Athari and Bahreini 2023), manufacturing (Sardo et al 2022), the financial sector (Boateng et al 2022), and the non-financial sector (Bazhair and Alshareef 2022;Khan et al 2023). On the contrary, Yang et al (2015) concluded that almost all the studies carried out in China regarding debt examinations do not recognize differences among business sectors.…”
Section: Resultsmentioning
confidence: 99%
“…Although a higher level of indebtedness may not explicitly mean a negative, since the cost of equity capital is higher compared to the cost of foreign capital (Valaskova et al, 2019), it is nevertheless true that the higher the indebtedness of the firm, the greater the risk of the business arises, which results in a more difficult acquisition of debt financing (Durana et al, 2021). Another reason why high indebtedness does not necessarily mean a negative is that its growth contributes to increasing profitability or market value (Kovacova et al, 2022), but only in financially stable companies (Ruckova & Skulanova, 2022). There is also no direct connection between indebtedness and the insolvency of a firm, because a higher level of corporate debt does not automatically lead to insolvency (Krabec & Cizinska, 2022), and therefore it is necessary to compare these indicators with liquidity indicators (Zaremba, 2016).…”
Section: Resultsmentioning
confidence: 99%